PENGELOLAAN PAJAK RESTORAN DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH PADA BADAN PENDAPATAN DAERAH KOTA KENDARI - Sartono; Sahrun; Fitrida (Halu Oleo University, 2022)
This study aims to determine the management of restaurant taxes and their contribution to local revenue in the Kendari City Regional Revenue Agency. The method used in this research is descriptive qualitative. Data collection techniques through literature review and field research, obtained from observations, interviews and documentation. The research location is the Regional Revenue Agency of Kendari City. The results show that the restaurant tax management carried out by the Kendari City Regional Revenue Agency so far has been quite good but still not optimal, it can be seen from the presentation between the target and the realization of restaurant tax revenues from 2018-2020 experiencing fluctuations and in 2019 the achievement is very far. of the specified target, as well as the last 3 years the contribution of restaurant tax to Regional Original Income (PAD) is very small. This is because there are still many obstacles experienced by the Kendari City Regional Revenue Agency in managing restaurant taxes. These obstacles include the lack of awareness of taxpayers, the lack of personnel in the restaurant tax sector and the Covid-19 pandemic